Brand Preferences, Social Influences and the Stated Needs of the Adolescent Shopper: An Insider's Perspective - Koukidis, Nikolaos (2007)
The subject of adolescent consumer behaviour is explored in the present study, by concentrating on a segment of the total market, specifically the affluent adolescents; students of private schools in Athens, Greece. The research brings together issues of adolescent consumer behaviour, brand preferences, brand relationships, susceptibility to interpersonal influences, reference groups and impulse purchases. Current knowledge has not focused on the variable of socioeconomic background, and does not provide sufficient understanding of how the issues mentioned above are perceived to interact. Moreover, current knowledge is based largely on old researches and the social evolution of this age group might have had an impact on consumer behaviour. Middle-upper class adolescents are an important segment as they have greater spending power and shopping involvement. An insider's account is needed create a profile of the market segment. By conducting a qualitative interpretative research, the subject is explored inclusively, and valuable theoretical contribution is achieved. Twenty informants were interviewed and the material was analysed thematically. Findings indicate that shopping is a complex yet joyful activity for adolescents, who appear to be keen on information searching. Experiential knowledge and anticonformity (Lin et al., 2007) are the primary drivers of brand relationships, which were few and weak, and the criteria for their brand repertoire (Ehrenberg, 2000) preferences. Price is an important concluding criterion, whereas likeness and quality is the initial one, influencing the need's intensity. Middle upper class adolescents are market mavens (Goldsmith et al., 2003) displaying utilitarian and hedonic shopping orientation simultaneously. Normative reference groups are found to be reprehensible and avoided as they are endangering the individual's uniqueness. Adolescent's viewpoint of consumption is believed to differ from the adults cost-effective thinking (Ahava et al., 2004), but this study suggests it is even more advanced in some cases, being benefit-effective, not as superficial as described in the literature. Three concepts are defined, contributing insights to consumer behaviour theory. The current literature is enriched by the differentiation of economic and recreational shoppers' (Bellenger et al., 1980), who in the present research are described as logical and spontaneous due to their special characteristics and versatile behaviour. Also, a theoretical contribution of this study is the creation of the stated needs dimensions conceptualised to place needs in four major categories according to how they are described and assist in predicting consumer action. Finally, a new type of reference group is defined, individualistic reference group which benefits its members psychologically in a similar way similarly to how utilitarian and value-expressive reference groups do; however members don't have the tendency to comply with any consumption or behavioural rules.